Adipose-Derived Extracellular Vesicles: Systemic Messengers and Metabolic Regulators in Health and Disease - Bond, Simon T.; Calkin, Anna C.; Drew, Brian G. (Frontiers in Physiology, 2022)
Adipose tissue is comprised of a heterogeneous population of cells, that cooperate to perform diverse physiological roles including endocrine related functions. The endocrine role of adipose tissue enables it to communicate nutritional and health cues to other organs such as the liver, muscle and brain, in order to regulate appetite and whole-body metabolism. Adipose tissue dysfunction, which is often observed in obesity, is associated with changes in the adipose secretome, which can subsequently contribute to disease pathology. Indeed, secreted bioactive factors released from adipose tissue contribute to metabolic homeostasis and likely play a causal role in disease; however, what constitutes the entirety of the adipose tissue secretome is still poorly understood. Recent advances in nanotechnology have advanced this field substantially, and have led to the identification of small, secreted particles known as extracellular vesicles (EVs). These small nano-sized lipid envelopes are released by most cell types, and are capable of systemically delivering bioactive molecules such as nucleic acids, proteins and lipids. EVs interact with target cells to deliver specific cargo that can then elicit effects in various tissues throughout the body. Adipose tissue has recently been shown to secrete EVs that can communicate with the periphery to maintain metabolic homeostasis, or under certain pathological conditions, drive disease. In this review, we discuss the current landscape of adipose tissue derived EVs, with a focus on their role in the regulation of metabolic homeostasis and disease pathology.